Peningkatan Kapasitas Kader Posyandu melalui Edukasi Deteksi Dini Kasus Lumpuh Layuh Mendadak di Wilayah Kerja Puskesmas Ophir Kabupaten Pasaman Barat - Ane Dayu Perwati; Masrizal Masrizal; Nailul Hikmi; Falah Fauzi (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
Acute flaccid paralysis (AFP) is a serious clinical condition that can be an early sign of polio disease. Since the discovery of a new polio case in Aceh in late 2022, Indonesia has experienced another polio outbreak after being declared polio-free in 2014. Early detection of AFP is critical to ensure no transmission of wild polio cases in the community. AFP case finding in Ophir health center working area of West Pasaman district is low. Therefore, cadre strengthening is needed to improve their capacity to detect and report AFP cases. Through this activity, cadres gained knowledge and practical skills to recognize AFP signs and symptoms, conduct early reporting, and support rapid case follow-up. This activity was conducted in Jorong Pujorahayu in September 2025 involving 20 posyandu cadres. Methods used were pre-test, education through interactive lecture, discussion, reporting simulation, and post-test. Data analysis used the Wilcoxon test. The results showed a significant increase in knowledge, attitudes, and actions of cadres after the intervention (p<0.05). The average knowledge increased from 3.65 to 5.00, attitude from 4.40 to 5.00, and action from 4.30 to 5.00. Interactive education was effective in building cadre readiness to detect and report AFP cases early. In addition, the activity had positive impacts such as strengthening polio surveillance network and providing educational media. In conclusion, this activity has successfully improved cadre capacity and strengthened community-based reporting system. It is recommended that similar activities be conducted continuously at the PHC level to prevent wild polio transmission in the community.